The Application of a Combined Online and Offline Health Intervention Model for Assessing Parents' KAP About Testicular Torsion: A Self‐Controlled Study - Qin Xia; Chengli Wu; Yanjun Gou; Ruixia Wang (Nursing Open, 2025)
ABSTRACT Aim To assess the efficacy of a combined online and offline health intervention model tailored to the needs of the study population in the levels of knowledge, beliefs and behaviours of parents about testicular torsion. Design A cross‐sectional and a self‐controlled study. Methods From March to July 2023, a convenience sampling method was employed to select 500 parents of male children from a kindergarten and a primary school in a city in Guizhou Province, China. A pre‐ and post‐intervention survey was conducted utilising a self‐designed questionnaire to assess the parents' existing knowledge, beliefs and behaviours concerning testicular torsion. This survey utilised a design tailored to the study, incorporating both before and after control measures. Results A total of 476 children's parents completed a 3‐month health intervention in this study. Knowledge of testicular torsion among children's parents increased from 21.71% before the intervention to 74.85% after the intervention, and the difference was statistically significant (χ2 = 3767.559, p < 0.001); children's parents' attitude scores toward testicular torsion increased from (35.72 ± 3.55) before the intervention to (39.84 ± 2.56) after the intervention, and the difference was statistically significant (t = 20.193, p < 0.001); and the behavioural scores of children's parents toward testicular torsion increased from (15.72 ± 3.02) points before the intervention to (38.08 ± 1.62) points after the intervention, with a statistically significant difference (t = 137.454, p < 0.001). Conclusion The health intervention, combining both online and offline methods, significantly improved parental knowledge of testicular torsion. It also effectively shifted parental beliefs and behaviours toward more proactive management of the condition. This model demonstrates considerable potential for practical implementation of testicular torsion knowledge among parents, thereby potentially reducing critical response times in clinical scenarios. Impact The current study highlights the effectiveness of a comprehensive health intervention model that integrates online and offline components in enhancing the knowledge and beliefs of parents regarding testicular torsion. Additionally, it provides novel insights for enhancing parental knowledge and beliefs about testicular torsion, aiming to mitigate prehospital delays and reduce the likelihood of orchiectomy. Reporting Method Study methods and results reported in adherence to the STROBE checklist. Patient or Public Contribution No patient or public contribution.